Catchment‐scale Phosphorus Export through Surface and Drainage Pathways. Issue 1 (1st January 2019) - Brendel, Conrad E.; Soupir, Michelle L.; Long, Leigh Ann M.; Helmers, Matthew J.; Ikenberry, Charles D.; Kaleita, Amy L.
Abstract : The site‐specific nature of P fate and transport in drained areas exemplifies the need for additional data to guide implementation of conservation practices at the catchment scale. Total P (TP), dissolved reactive P (DRP), and total suspended solids (TSS) were monitored at five sites—two streams, two tile outlets, and a grassed waterway—in three agricultural subwatersheds (221.2–822.5 ha) draining to Black Hawk Lake in western Iowa. Median TP concentrations ranged from 0.034 to 1.490 and 0.008 to 0.055 mg P L −1 for event and baseflow samples, respectively. The majority of P and TSS export occurred during precipitation events and high‐flow conditions with greater than 75% of DRP, 66% of TP, and 59% of TSS export occurring during the top 25% of flows from all sites. In one subwatershed, a single event (annual recurrence interval < 1 yr) was responsible for 46.6, 84.0, and 81.0% of the annual export of TP, DRP, and TSS, respectively, indicating that frequent, small storms have the potential to result in extreme losses. Isolated monitoring of surface and drainage transport pathways indicated significant P and TSS losses occurring through drainage; over the 2‐yr study period, the drainage pathway was responsible for 69.8, 59.2, and 82.6% of the cumulative TP, DRP, and TSS export, respectively. Finally, the results provided evidence that particulate P losses in drainage were greater than dissolved P losses. Understanding relationships between flow, precipitation, transport pathway, and P fraction at the catchment scale is needed for effective conservation practice implementation. Core Ideas: Single events accounted for the vast majority of annual P and total suspended solids export. Frequent, low‐depth events resulted in extreme P and total suspended solids losses. Particulate P losses in drainage waters can exceed dissolved P losses.